2017
DOI: 10.1186/s12877-017-0675-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sedentary behavior and physical activity with older adults’ physical function: an isotemporal substitution approach

Abstract: BackgroundsThe purpose of this study was to examine, in a sample of Japanese older adults, the associations of objectively-assessed sedentary behavior (SB) and physical activity (PA) with performance-based physical function. The isotemporal substitution (IS) approach was used to model simultaneously the effects of the specific activity being performed and the activity being displaced, in an equal time-exchange manner.MethodsAmong 287 older adults (65–84 years), we used accelerometers to identify the daily aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 33 publications
7
74
0
Order By: Relevance
“…the sum of time spent in sedentary activity, LPA, and MVPA), were simultaneously entered into the model. The details of this statistical model are described by Yasunaga et al (). The isotemporal substitution model (in the case of omitting sedentary activity) was expressed as equation 3 as follows: Sleep parameters variable=LPA+MVPA+total wear time+confounding factors …”
Section: Methodsmentioning
confidence: 99%
“…the sum of time spent in sedentary activity, LPA, and MVPA), were simultaneously entered into the model. The details of this statistical model are described by Yasunaga et al (). The isotemporal substitution model (in the case of omitting sedentary activity) was expressed as equation 3 as follows: Sleep parameters variable=LPA+MVPA+total wear time+confounding factors …”
Section: Methodsmentioning
confidence: 99%
“…A series of partition models and isotemporal substitution models (19) were used for each type of cancer to examine the associations of daily TV screen time, time spent walking/day, time spent in moderate-intensity physical activity/day, time spent in vigorous-intensity physical activity/day and cancer incidence (19,(31)(32)(33)(34). Partition models examined all behaviours simultaneously, without adjusting for total physical activity time.…”
Section: Cancer Ascertainmentmentioning
confidence: 99%
“…Associations were more likely observed in clinical populations (5 out of 7 studies; 71%) 81,106,[111][112][113] compared with community-dwelling samples (11 out of 21 studies; 52%). 101,102,109,110,117,118,[122][123][124]126,128 All seven longitudinal studies found a detrimental association of sedentary time with physical function; i.e., more sedentary time was associated with poorer physical function. 109,110,113,[115][116][117][118] The following sections describe the studies in the categories in the figure in greater detail.…”
Section: Overall Findingsmentioning
confidence: 99%
“…Of the papers included, 10 used self-report measures of sedentary behaviour, 81,100,103,109,110,113,115,116,119,120 15 used activity monitors to assess sedentary time, 101,102,[104][105][106]108,112,117,[121][122][123][124][125][126][127] and three used both. 111,114,128 Eleven different objective devices were used to assess sedentary behaviour, of which four were a posture monitor (used in three studies [10%]).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation